Higher Educations Employees Work From Home Productivity During The Covid-19 Outbreak: The Role Of Motivation As Mediator - Noral Hidayah Alwi; Zahir Osman; Zulaihan Ismail; Bibi Nabi Ahmad Khan (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
This study aims to evaluate the mediating effect of employees’ motivation on the relationship among workplace environment, organizational support, and employees’ work from home productivity among higher education institutions in Malaysia during the Covid-19 pandemic. For item measurement and structural model assessment, the Structural Equation Modeling (SEM) utilizing Partial Least Square (PLS) technique was adopted. A total of 579 clean and usable data was analyzed and the findings showed that there was a positive and significant direct effect between workplace environment and organizational support with motivation. However, direct effect on productivity, only the workplace environment was significant. Then, the direct effect between motivation and productivity was also found to be significant. Then for the mediating relationships, the result showed that motivation mediated the relationship of the workplace environment and organizational support with productivity where both mediating relationships were significant. Higher education institutions should put more attention to enhance the workplace environment, organizational support, and motivation to achieve higher employees’ productivity during work from home in any crisis in the future. The findings also provided a direction for the higher education institutions in executing a policy of work from home for their employees.